Identifying the mechanisms that contribute to safe and effective electronic test result management systems— a multisite qualitative study. (6th November 2021) - Georgiou, Andrew; Li, Julie; Thomas, Judith; Dahm, Maria R
Abstract: Objective: Suboptimal design of health information technology (IT) systems can lead to the introduction of errors in the diagnostic process. We aimed to identify mechanisms that can affect the safety and effectiveness of these systems in hospital settings thus contributing to the building of an explicit and replicable understanding of the variables that can affect the functioning of IT systems. Materials and Methods: This qualitative study drew from observations and semistructured interviews from a purposive sample of 46 participants (26 emergency department and 20 laboratory and medical imaging staff) across 3 Australian hospitals. Iterative, inductive coding of the data led to the development of higher-level themes based on relationships between codes. Results: Two overarching themes emerged: (1) usability and safety of the electronic test result management system; and (2) system redesign considerations about who is meant to follow up, when and how. The usability and safety of digital systems and the way these systems deal with accountability processes are triggered by mechanisms that are contextually dependent. Discussion: Our findings highlighted the multitransactional nature of the test result management process involving numerous healthcare professionals across different settings. This communication requires integration of the systems utilized by different departments and transparency of the test result follow-up process to facilitate clear lines of responsibility and accountability. Conclusion: Identifying mechanisms that shape the functionality and sustainability of electronic result management can offer a valuable appreciation of key elements that need to be accounted for, and the circumstances in which they need to operate effectively.